TEKNIK PENERJEMAHAN PADA BUKU CERITA ANAK DWIBAHASA DI PROVINSI BANTEN: en_US - Bachtiar, Anitawati; en_US, en_US (Kementerian Sekretariat Negara Republik Indonesia, 2024)
Translation techniques are critical in preserving the meaning and cultural context of texts from the source language to the target language. Each technique plays a vital role in addressing various linguistic and cultural challenges that arise during the translation process. This study aims to analyze the translation techniques used in bilingual children's storybooks from the Banten Province. This study uses data from 13 Sundanese-Indonesian books. The texts in these bilingual books were analyzed using Molina and Albir’s translation technique theory, as cited in Supriatnoko (2022:199). According to the analysis of 689 data points, literal translation techniques dominated with 581 uses (85%), followed by modulation, transposition, adaptation, free translation, omission, and addition. The findings indicate that translators tend to favor techniques that preserve the original structure and meaning of the source text, although in some cases, adjustments were made to ensure clarity and fluency in the target language. This study also emphasizes the importance of translation techniques in documenting and preserving regional language vocabulary, particularly in Banten's local culture.